Papo de criança: um encontro para além do museu - Greciene Lopes dos Santos (2014)
In this paper, we draw similarities between the areas of education, communication, museum and heritage. The search has two aims; the first one is to analyse the radio emition of Programa: Papo de criança1, from Museu Casa Guignard (1994-1996). To do so, we raise its caracteristics in relation to its organization, content and actors, identifying the different speeches that were present on its construction. The second is whether it is possible to establish a communicative contract based on heritage education during a radio program produced by an art museum. The presented results affirm that the program Papo de Criança has specific indicators of radio support; it was an educational program, has developed a role on the promotion and dissemination of the cultural heritage from Ouro Preto. The contract of communication established between the producers and listeners bolstered up on heritage education, and promoted the linear unpacking of themes; privileged the voice of the expert in full-time programs. Moreover, the cultural heritage from Ouro Preto was the main theme on discussion. The museum was seen as an inseparable part of the city of Ouro Preto, being known as the place of knowledge and doing. Thus, the listener was asked to reflect on their culture and heritage, assuming that, to preserve it, it takes involvement and knowledge.